STUDY ON THE CREATIVITY OF THE ENTREPRENEURIAL BUSINESS - Kyurova, Vyara (Revista Inclusiones, 2020)
The article presents the results of a study on the creativity of the entrepreneurial business in Bulgaria. The aim is to clarify the specifics of creativity of the entrepreneurial business and to identify its main problems. The assessment of creativity of the entrepreneurial business is based on the results of a survey of 58 representatives of the entrepreneurial business in Bulgaria. The theoretical aspects of creativity are examined. Based on a survey, the main problems related to the creativity of the entrepreneurial business in Bulgaria have been identified.